Validity, reliability and clinical utility of ASSIST-Y in assessing risk of substance-related harm and dependence in Spanish male adolescents - Núria Ibáñez-Martínez; Matthew William Richard Stevens; Núria Civit-Bel; Noemí Moreno-Ferrer; Sandra Lopez-Ferré; Ana Olivares-Casado; Juame Claramunt-Mendoza; Chris Holmwood; Robert Ali (Child and Adolescent Psychiatry and Mental Health)
Abstract Background Substance use among adolescents is strongly associated with adverse physical, mental health, and social outcomes. Prevention and early intervention can reduce the likelihood of future problems, but requires valid and reliable screening tools capable of assessing risk across a range of substances. This study assessed the validity, reliability, and clinical utility of the Alcohol, Smoking and Substance Involvement Screening Test (ASSIST-Y) for adolescents aged 15–17 years. Methods A sample of adolescent males (N = 101), aged 15–17 years, held in a juvenile detention facility on substance-related offences in Barcelona, Spain were eligible. Participants were administered a battery of standardized substance-use screening tools by a clinical psychologist, and underwent a diagnostic interview assessing DSM-IV-TR substance abuse and dependence by an addiction medicine specialist. Scores on the various assessments were compared to establish validity (concurrent with interview, convergent with other measures), reliability, and clinical utility of ASSIST-Y. Results Majority of participants (n = 77) completed assessments. While tobacco was not assessed as part of the interview, concurrent validity in detecting substance abuse was established for all remaining substances. Concurrent validity for detecting dependence was established for alcohol, cannabis, cocaine, stimulants and sedatives. Fewer numbers in higher-risk groups for inhalants, opioids and hallucinogen use limited confirmation of validity for those substances. ASSIST-Y also demonstrated good convergent validity with the other screening tools for all substances, except hallucinogens. Reliability for each subscale was established, except for tobacco (too few items), sedatives, and hallucinogens. Finally, clinical utility indices were significant for most substances (except sedatives and opioids); whilst clinical utility indices were significant for ruling out cases of non-dependence (all substances). Conclusions As a screening tool, the purpose of ASSIST-Y is designed to help identify adolescents who may be at-risk of substance-related harm. While the instrument was found to be valid and reliable in identifying risky use across a variety of substances, further research is needed to validate the instrument in other population groups, and for other substances. Future research should investigate the effect of the linked brief intervention to reduce risk of harm, especially for non-specialist clinicians.